Determination of Storage Time of Saliva Samples Obtained From Patients With and Without Chronic Periodontitis for the Comparison of Some Biochemical and Cytological Parameters - YARAT, AYŞEN; AK, ESİN (WILEY, 2013)
Background: Salivary glutathione (GSH), malondialdehyde (MDA), protein, sialic acid (SA) levels, cytological parameters, and tissue factor activities (TFa) were investigated when fresh and after 3, 7, 11, 15, 21, and 30 days (d) of storage at -20 degrees C both in the control and the periodontitis group. Moreover, the control and the periodontits groups were compared and continuity of the significances detected between the two groups were evaluated. Methods: GSH, MDA, SA, protein, and TFa were determined using the methods of Beutler, Yagi, Warren, Lowry, and Quick, respectively. Saliva imprint samples were stained with Giemsa and microscopically examined. Results: When the continuity of the significances of differences between the two groups was investigated, differences continued to be significant for GSH and TFa on days 3, 7, 11, 15, 21, and 30. Cytologically, only the significance detected between leucocyte numbers continued to be significant for 30d. However significance of differences in total protein, MDA, and SA levels on day 0, were interrupted on days 3, 7, and 11, respectively. Conclusion: Saliva samples may be stored for 30d for GSH and TFa analyses in patients with and without periodontitis. However, to compare salivary MDA, SA, and total protein levels in these groups we suggest fresh samples to be studied. (C) 2013 Wiley Periodicals, Inc.
Keywords: saliva; storage; periodontitis; TISSUE FACTOR ACTIVITY; ANTIOXIDANT CAPACITY; LIPID-PEROXIDATION; CREVICULAR FLUID; DISEASE; ASSAY; GLUTATHIONE; INDUCTION; BLOOD; SERUM